Pengaruh Kepercayaan, Pengetahuan dan Sikap Terhadap Akses Jamban Di Perkotaan - Mila Mardotillah; Budhi Gunawan; Rini S. Soemarwoto; Ardini S. Raksanagara (Jurnal Sosial Humaniora, 2025)
The difficult access of urban healthy latrines is influenced by population density, limitation of infrastructure and high mobility. Cultural factors become one of the keys in influencing people behavior to access healthy latrines. The aim this research was to explore the cultural factors influencing the people to access the healthy latrine. The method used was a retrospective quantitative approach with cross sectional analytical method (cross sectional) in order to know the cultural factors that influence people behaviour in using healthy latrines. The research found that the cultural factors related to access of healthy latrines include belief on the taboo, gender, beliefs and differences of each generation. The significant influential factors are trust, knowledge and attitude. While other factors simultaneously affect the citizen in behaving toward using healthy latrines. The conclusion was that the behaviour in accessing healthy latrines is created by individual’s knowledge, attitudes and actions. The behaviour will be established and successful if the cultural factor approach is carried out simultaneously. The individual’s concept about something is the impact of the individual’s way of thinking about something based on the culture containing non-individual but public meaning. So, when the system of meaning belongs to the collective society, society can have the same pattern of behaviour. The cultural factors can serve as a basis for improving urban residents' access to healthy latrines.